Immunological Markers in Chronic Kidney Disease: Diagnostic and Prognostic Implications - Muhammed, Thikra Majid (American Journal of Biology and Natural Sciences, 2025)
Chronic kidney disease (CKD) is a progressive disorder characterized by a gradual loss of renal function, often leading to end-stage renal disease and significant morbidity. Recent research has highlighted the role of immunological markers in the pathophysiology, diagnosis, and prognosis of CKD. Immune dysregulation, including both innate and adaptive responses, contributes to persistent inflammation and tissue damage, accelerating disease progression. Among the most studied biomarkers are pro-inflammatory cytokines such as interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and interleukin-1 beta (IL-1β), which are elevated in CKD patients and associated with renal fibrosis and cardiovascular complications. Anti-inflammatory cytokines, particularly interleukin-10 (IL-10), play a protective role, and their imbalance reflects immune dysfunction. Additionally, high-sensitivity C-reactive protein (hs-CRP) and other acute-phase proteins serve as systemic indicators of chronic inflammation and correlate with poor outcomes. Novel markers, including monocyte chemoattractant protein-1 (MCP-1), soluble CD163, and circulating adhesion molecules, have been proposed as predictors of progression to advanced CKD stages. Beyond diagnosis, immunological markers are increasingly valuable for prognosis, as they can predict complications such as anemia, malnutrition, and cardiovascular disease, which remain leading causes of mortality in CKD patients. The integration of immunological markers into clinical practice may enhance early detection, improve risk stratification, and guide individualized therapeutic strategies. Future research should focus on standardizing biomarker panels and validating their clinical utility across diverse patient populations. Understanding the immunological landscape of CKD not only deepens insights into its pathogenesis but also opens new avenues for targeted therapies and improved patient management.